A novel extendable multilevel inverter for efficient energy conversion with fewer power components: Configuration and experimental validation - Meraj, Sheikh Tanzim; Yu, Samson Shenglong; Rahman, Md. Siddikur; Arefin, Ahmed Amirul; Lipu, Molla Shahadat Hossain; Trinh, Hieu (International journal of circuit theory and applications, 2024)
Summary Multilevel inverters (MLIs) are widely used in various sectors of power electronics. Some major benefits of using MLI are the high‐quality voltage output, harmonic reduction, and efficiency. However, MLIs also bear a range of disadvantages including an excessive number of components, high total standing voltage (TSV), and complicated control scheme. Thus, a novel cross‐switched neutral point clamped (CSNPC) nine‐level inverter is proposed. Many of the suggested MLIs use a large number of DC supplies and additional switches that are not fully utilized and generate high power loss. However, the proposed MLI topology has a smaller number of power electronic switches and DC supplies, leading to higher energy efficiency. Moreover, a simplified high frequency modulation technique, named hysteresis‐band‐based discontinuous pulse width modulation (DPWM) is devised to control the proposed MLI. This modulation scheme has effectively minimized capacitor voltage imbalance. Furthermore, the designed structure is extendable to a modular MLI, without any additional H‐bridge circuit. To verify its benefits over other recent similar types of MLIs, a thorough comparison is presented for the number of components and power losses. The proposed MLI has showed 95.54% efficiency, and the modular CSNPC can achieve a total harmonic distortion (THD) of 6.43%. A 9‐level cross‐switched neutral point clamped (CSNPC) multilevel inverter (MLI) with reduced number of power electronics components.